Surprises according to Humphrey - Birney, Betty G. (Birney, Betty G. Humphrey adventures, 2008)
While continuing to help his classmates solve their problems, Humphrey, pet hamster of Longfellow School's Room 26, faces many surprises, like rolling in a hamster ball, a substitute janitor who might be an alien, and the possibility of Mrs. Brisbane retiring.